Period and Hero in the Work of “O`Tgan Kunlar” (Texas Journal of Multidisciplinary Studies, 2022)
In this article, it is written about Abdulla Kadiri's novel "Otgan kunlar", its characters, description of the work. Opinions related to the work are presented.